PENGARUH WORK FAMILY CONFLICT DAN STRES KERJA TERHADAP KEPUASAN KERJA WANITA MENIKAH - Mentiana Sibarani; Nathasya Stefhany (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Nowadays, many married women decide to work. There are many benefits that they can get from working, but of course it triggers multiple role conflicts and work stress which causes their job satisfaction to decrease. The purpose of this study was to examine the effect of work family conflict and work stress on job satisfaction of married women who work. This research method is causal associative research. The data used in this study is quantitative data and the data sources use primary and secondary data. Primary data was obtained through a questionnaire distributed to 150 respondents based on the calculation of the Hair Formula method and secondary data was obtained from a literature study. The population of this study is married women who work, using the Nonprobability Sampling method and purposive sampling that married women working with the age of 20 years to 30 years. After the data is obtained, it is tested using the IBM SPSS Statistics 22 application, the results obtained are that there is a simultaneous influence of work family conflict and work stress variables on job satisfaction which is carried out using the F test where the value of sig (0.000) is smaller than 0, 05. The results of the T-test conducted showed that the work family conflict variable had no effect on the job satisfaction variable with a value of sig (0.202) greater than 0.05 so Ho was accepted. And the work stress variable has an effect on the job satisfaction variable with a value of sig (0.009) smaller than 0.05 so that Ho is rejected. Based on the results of the influence of work family conflict and work stress variables on job satisfaction, that is 11.5% while 88.5% is influenced by other factors outside the work family conflict and work stress variables.